Hepatic insulin resistance in ob/ob mice involves increases in ceramide, aPKC activity, and selective impairment of Akt-dependent FoxO1 phosphorylation - Mini P. Sajan; Robert A. Ivey; Mackenzie C. Lee; Robert V. Farese (Journal of Lipid Research, 2015)
Pathogenesis of insulin resistance in leptin-deficient ob/ob mice is obscure. In another form of diet-dependent obesity, high-fat-fed mice, hepatic insulin resistance involves ceramide-induced activation of atypical protein kinase C (aPKC), which selectively impairs protein kinase B (Akt)-dependent forkhead box O1 protein (FoxO1) phosphorylation on scaffolding protein, 40 kDa WD(tryp-x-x-asp)-repeat propeller/FYVE protein (WD40/ProF), thereby increasing gluconeogenesis. Resultant hyperinsulinemia activates hepatic Akt and mammalian target of rapamycin C1, and further activates aPKC; consequently, lipogenic enzyme expression increases, and insulin signaling in muscle is secondarily impaired. Here, in obese minimally-diabetic ob/ob mice, hepatic ceramide and aPKC activity and its association with WD40/ProF were increased. Hepatic Akt activity was also increased, but Akt associated with WD40/ProF was diminished and accounted for reduced FoxO1 phosphorylation and increased gluconeogenic enzyme expression. Most importantly, liver-selective inhibition of aPKC decreased aPKC and increased Akt association with WD40/ProF, thereby restoring FoxO1 phosphorylation and reducing gluconeogenic enzyme expression. Additionally, lipogenic enzyme expression diminished, and insulin signaling in muscle, glucose tolerance, obesity, hepatosteatosis, and hyperlipidemia improved. In conclusion, hepatic ceramide accumulates in response to CNS-dependent dietary excess irrespective of fat content; hepatic insulin resistance is prominent in ob/ob mice and involves aPKC-dependent displacement of Akt fromWD40/ProF and subsequent impairment of FoxO1 phosphorylation and increased expression of hepatic gluconeogenic and lipogenic enzymes; and hepatic alterations diminish insulin signaling in muscle.